Heat propagation around a nanothermal rod in asphalt concrete: Multiscale modeling and experimental characterization - Jianguo Wu; Qingzhi Wang; Jianhong Fang; Anhua Xu (Case Studies in Construction Materials, 2025)
Ice formation on pavement surfaces near tunnel openings in alpine regions poses significant safety risks. While nanothermal rod offer a promising solution, their heat transfer mechanisms and thermal-affected range in asphalt concrete remain poorly understood, particularly regarding interfacial thermal resistance and heat propagation in heterogeneous materials. This study establishes a multiscale heat transfer model to analyze the spatiotemporal temperature distribution around a nanothermal rod embedded in asphalt concrete. The model incorporates effective thermal conductivity of the composite and boundary conditions reflecting realistic pavement environments. Numerical simulations validate the model’s accuracy, demonstrating a 98 % agreement with experimental data under varying power inputs (10–40 W/m) and ambient temperatures(−20°C to −5°C). Laboratory experiments using infrared thermography further confirm that the effective heat transfer radius reaches 7 cm at −5°C with 30 W/m heating, enabling a recommended rod spacing of 10 cm for uniform deicing. This study provides technical support for practical deicing systems through the innovation of the multiscale heat transfer model and the reliability of experimental validation, and offers a solid theoretical basis for the design of pavement thermal management systems.